Vitamin D-dependent induction of cathelicidin in human macrophages results in cytotoxicity against high-grade B cell lymphoma - Bruns, Heiko; Büttner, Maike; Fabri, Mario; Mougiakakos, Dimitrios; Bittenbring, Joerg T.; Hoffmann, Markus; Beier, Fabian; Pasemann, Shirin; Jitschin, Regina; Hofmann, Andreas D.; Neumann, Frank; Daniel, Christoph; et al. (Science Translational Medicine, 2015)
Infiltration by macrophages represents a characteristic morphological hallmark in high-grade lymphatic malignancies such as Burkitt's lymphoma (BL). Although macrophages can, in principle, target neoplastic cells and mediate antibody-dependent cellular cytotoxicity (ADCC), tumor-associated macrophages (TAMs) regularly fail to exert direct cytotoxic functions. The underlying mechanisms responsible for this observation remain unclear. We demonstrate that inflammatory M1 macrophages kill proliferating high-grade B cell lymphoma cells by releasing the antimicrobial peptide cathelicidin in a vitamin D-dependent fashion. We show that cathelicidin directly induces cell death by targeting mitochondria of BL cells. In contrast, anti-inflammatory M2 macrophages and M2-like TAMs in BL exhibit an altered vitamin D metabolism, resulting in a reduced production of cathelicidin and consequently in inability to lyse BL cells. However, treatment of M2 macrophages with the bioactive form of vitamin D, 1,25D3, or a vitamin D receptor agonist effectively induces cathelicidin production and triggers tumoricidal activity against BL cells. Furthermore, rituximab-mediated cytotoxicity of vitamin D-treated M2 macrophages is cathelicidin-dependent. Finally, vitamin D treatment of 25-hydroxyvitamin D (25D)-deficient volunteers in vivo or primary TAMs in vitro improves rituximab-mediated ADCC against B cell lymphoma cells. These data indicate that activation of the vitamin D signaling pathway activates antitumor activity of TAMs and improves the efficacy of ADC
EVALuna2:13103